2017
DOI: 10.1002/polb.24374
|View full text |Cite
|
Sign up to set email alerts
|

Properties of In situ polymerized poly(3,4‐ethylenedioxythiophene)/alumina composites for energy storage applications

Abstract: Composites formed by poly (3,4-ethylenedioxythiophene) and alumina (PEDOT/Al 2 O 3 ) have been prepared by in situ anodic polymerization. For this purpose, the stability of 1:1 and 4:1 monomer:alumina aqueous solutions has been examined as a function of the pH (2.3, 4.0, 7.0, 8.8 or 10.8). Results indicate that the monomer behaves as a dispersant that remains stable at the studied basic pHs despite they are close to the isoelectric point of alumina. Although the thermal stability of the composites is consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Thus, the incorporation of CP inside the dielectric hydrogel matrix does not cause an increment in the electrochemical activity, even though the oxidation and reduction of PEDOT and PHMeDOT are typically detected. 37 The first oxidation peak of chains occurs at 0. Table 1.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the incorporation of CP inside the dielectric hydrogel matrix does not cause an increment in the electrochemical activity, even though the oxidation and reduction of PEDOT and PHMeDOT are typically detected. 37 The first oxidation peak of chains occurs at 0. Table 1.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…[27][28][29][30] The unique characteristics of PEDOT are due to the oxygen atoms attached at the ,'-positions of the thiophene ring, which induce strong electron-donating effects and prevent the formation of parasitic - linkages during the polymerization of the 3,4ethylenedioxythiophene (EDOT) monomers. 31 Moreover, the electrochemical performance of PEDOT can be improved if properly combined with other materials such as graphene, 23,[32][33][34] carbon nanotubes, 35 inorganic oxides, 36,37 and even biomolecules. 26,[38][39][40][41] The present work represents a step ahead with respect to the setup of ESCs composed of PEDOT electrodes and γ-PGA solid electrolytic medium.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that GCD cycles are much less aggressive than CV cycles. Thus, previous studies showed that potentiostatic redox cycles alter drastically the structure of polymers [ 48 , 49 ]. This feature explains that AC values derived from GCD measures are, in general, higher than those obtained using CV, as shown in Figure 5 c and Figure 7 c.…”
Section: Resultsmentioning
confidence: 99%
“…Al 2 O 3 particles were prepared introducing the properly mass quantity into a vial containing magnetic stirrers, which was placed in a vortex at maximum power during 2 hours. 39 After that, particles were homogenized using a mortar. The size of the particles was controlled by both dynamic light scattering (DLS) and scanning electron microscopy (SEM).…”
Section: Methodsmentioning
confidence: 99%
“…In a recent work, we proved that incorporation of alumina (Al 2 O 3 ) to PEDOT through in situ polymerization at pH 8.8 significantly improves the electrochemical activity of such EAP. 39 In this work we combine our previous experience on γPGA biohydrogels and Al 2 O 3 composites to develop a solid organic symmetric supercapacitor prototype containing the following elements: 1) two self-supported electrodes made of γPGA, PEDOT microparticles, poly(hydroxymethyl-3,4-ethylenedioxythiophene) (PHMeDOT), which is a PEDOT derivative with an exocyclic hydroxyl group that facilitates its preparation in aqueous environments, and Al 2 O 3 ; and 2) a solid supporting electrolyte composed by γPGA biohydrogel doped with NaHCO 3 . The elements of the prototype have been synthesized, characterized and subsequently assembled using simple and low-cost techniques.…”
Section: Introductionmentioning
confidence: 99%